Pengujian Black Box Testing Pada Sistem Pendukung Keputusan Penerima Beasiswa di SMK Tarbiyatul Ulum Karawang - Yusup Mad Cani; Hannie Hannie; Azhari Ali Ridha (Jurnal Ilmiah Wahana Pendidikan, 2023)
The quality of the software can be measured one of them by testing the functionality of the system whether the system is running as it should or not. To maintain this quality, we need a test to find out the functionality in the scholarship recipient's decision support system at SMK Tarbiyatul Ulum Karawang using the Black Box Testing method where this method tests the functionality of the scholarship recipient's decision support system. the test thoroughly checks all the functionality in the scholarship recipient's decision support system. From the results of the tests carried out, it was found that all the functionality of the scholarship recipient's decision support system was running properly and there was no functionality failure.